STRUKTUR GEOLOGI CEKUNGAN OMBILIN BERDASARKAN INTERPRETASI CITRA SATELIT - -, Yuyun Yuniardi (Bulletin of Scientific Contribution, 2010)
Interpretation of remote sensing data on Ombilin Basin has resulted Geological Map Interpretation of the basin which is containing information about geological structure of the Ombilin Basin. Further more, this geological structure can be divided into two periode which are Paleogene geological structure and Neogen geolocical structure.